PERBEDAAN FUNGSI KOGNITIF PADA LANSIA YANG KUALITAS TIDURNYA BAIK DAN BURUK DI BANJAR PEKEN DESA SUMERTA DENPASAR - I Wayan Widyantara, Putu Eka Widyadharma, IGN Budiarsa, AAA Meidiary (Neurona Majalah Kedokteran Neuro Sains, 2012)
BACKGROUND THE INCREASING OF AGE CAUSES DECREASE OF THE SLEEP PERIOD SLEEP DISORDERS AND COGNITIVE FUNCTION COMPLAINTS ARE FREQUENTLY REPORTED IN THE ELDERLY THE PREVALENCE OF SLEEP DISORDERS AND IMPAIRMENT OF COGNITIVE FUNCTION IN THE ELDERLY IS HIGH ABOUT 67 AND 1734 BUT THERE ARE ONLY A FEW OF STUDY ABOUT COGNITIVE FUNCTION IN ELDERLY WHO EXPERIENCE SLEEP DISTURBANCES IN INDONESIA